눈운동장애 없이 시력 저하를 보인 해면정맥동 내경동맥류 1예 - 김승훈; Seung Hoon Kim; 김선웅; Sun Woong Kim; 김범태; Bum Tae Kim; 장지호; Jee Ho Chang (Daihan angwa haghoi jabji, 2012)
목적: 해면정맥동 내에 위치한 내경동맥류는 일차적으로 눈운동장애를 보이며 해부학적 특성상 압박시신경병증만을 보이는 경우는 드물다. 저자들은 눈운동장애 없이 시력 및 시야 손상을 주소로 내원한 환자에서 자기공명영상을 시행하여 해면정맥동 내에 한정된 내경동맥류가 내경동맥의 침대돌기위 분절을 전위시켜 발생한 압박시신경병증을 발견하고 치료하였기에 보고하고자 한다. 증례요약: 40세 여자 환자가 우연히 발견된 우안의 시력 저하를 주소로 내원하였다. 우안에서 상대구심성동공운동장애가 있었으며 시야 검사상 우안의 삼사분맹을 보였다. 뇌 자기공명영상 검사상 내경동맥의 침대돌기위 분절을 상내측으로 전위시키는 해면정맥동 분절의 내경동맥류를 발견하였으며, 전위된 내경동맥이 전대뇌동맥과 중간대뇌동맥의 분지 직전부에서 우측 시신경교차 앞부분의 시신경을 직접 압박하고 있었다. 치료로 Guglielmi Detachable Coil 색전술을 시행하였고 이후 시력 및 시야 손상이 호전되었다. 결론: 해면정맥동 분절에 한정된 내경동맥류는 눈운동장애가 주 증상이나 내경동맥의 말단부인 침대돌기위 분절을 상방 전위시키는 경우 시신경병증만도 유발될 수 있음을 보고하는 바이다. Purpose: Oculomotor disturbance is the common manifestation of intracavernous carotid aneurysm cases. Intracavernous carotid aneurysms causing compressive optic neuropathy with no oculomotor disturbance are relatively rare due to their anatomical characteristics. We experienced a case of intracavernous carotid aneurysm which resulted in a shifted supraclinoid segment of the internal carotid artery, presenting with visual loss and visual field defect with no oculomotor disturbance. Case summary: A 40-year-old woman presented with loss of vision in the right eye. A relative afferent pupillary defect was observed in this eye. Visual field test showed quadranopsia in the right eye. Magnetic resonance imaging revealed that the intracavernous carotid aneurysm had shifted the supraclinoid segment of the internal carotid artery to the superomedial position. The right optic nerve was directly molded by the shifted supraclinoid segment of the internal carotid artery at the point of the bifurcation between the anterior cerebral artery and the middle cerebral artery. A Guglielmi detachable coil (GDC) embolization was performed successfully with no operational complications. Six months after coiling, best corrected visual acuity of the right eye was 1.0, and the visual field defect had recovered in all except the superior temporal field. Conclusions: Oculomotor disturbance is frequently associated with intracavernous carotid aneurysms. Nevertheless, optic neuropathy without oculomotor disturbance may be the only sign in patients with an intracavernous carotid aneurysm that causes shifting of the supraclinoid segment of the internal carotid artery.